2017
DOI: 10.1097/qad.0000000000001273
|View full text |Cite
|
Sign up to set email alerts
|

Development of HIV drug resistance and therapeutic failure in children and adolescents in rural Tanzania

Abstract: Objective:To investigate the prevalence and determinants of virologic failure and acquired drug resistance-associated mutations (DRMs) in HIV-infected children and adolescents in rural Tanzania.Design:Prospective cohort study with cross-sectional analysis.Methods:All children 18 years or less attending the paediatric HIV Clinic of Ifakara and on antiretroviral therapy (ART) for at least 12 months were enrolled. Participants with virologic failure were tested for HIV-DRM. Pre-ART samples were used to discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
103
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(132 citation statements)
references
References 32 publications
22
103
7
Order By: Relevance
“…The emergence of DRM in the plasma RNA leading to virological failure in children was reported previously although these DRMs were absent at baseline . Using paired NGS sequencing of the cell‐associated DNA at baseline and at month six after ART, we present the most credible evidence for the emergence of the drug‐resistant virus during early ART resulting in virological failure.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The emergence of DRM in the plasma RNA leading to virological failure in children was reported previously although these DRMs were absent at baseline . Using paired NGS sequencing of the cell‐associated DNA at baseline and at month six after ART, we present the most credible evidence for the emergence of the drug‐resistant virus during early ART resulting in virological failure.…”
Section: Discussionsupporting
confidence: 57%
“…The viral variants containing drug‐resistance mutations (DRMs) may have been transmitted to a newly infected individual before treatment initiation or may have evolved spontaneously in a chronically infected individual . The minority drug‐resistant viral variants can evolve upon ART initiation even if the preexisting DRMs were not detectable and can eventually impact treatment response …”
Section: Introductionmentioning
confidence: 99%
“…While viral load monitoring is becoming more routine in many LMIC and can be useful for identifying non-adherence, this strategy cannot determine whether viral non-suppression is due to adherence (as well as what type of adherence issues), drug resistance or some combination. Available data suggest drug resistance, particularly for older and more treatment experienced children, is increasingly common in LMIC [39][40][41]. The frequency of treatment interruptions in this cohort as measured by MEMS â highlights the potential risk for developing drug resistance with particular non-adherent behaviours.…”
Section: Discussionmentioning
confidence: 84%
“…Overall, studies conducted in Tanzania reported a prevalence of virological failure ranging from 19% to 61% and an over 75% prevalence of HIV-DRM. 10,[22][23][24][25] Several factors may have contributed to the observed virological efficacy of ART in our setting. First, unlike many other HIV treatment programmes in resource-limited settings, the CDCI is reasonably well staffed with physicians specifically dedicated to HIV treatment outcome in rural Tanzania JAC HIV treatment and care, including HIV specialists who continuously provide mentorship for capacity building to local medical practitioners.…”
Section: Discussionmentioning
confidence: 97%